Increasing fish farm profitability through aquaculture best management practice training in Egypt - Dickson, M.; Nasr-Allah, A.M.; Al-Kenawy, D.A.R.; Kruijssen, Froukje (Elsevier, 2016)
Egyptian aquaculture production has grown rapidly to over one million tons per year so that it now provides most of the country's fish supply. However, Egyptian fish farmers have received little extension advice or training. An intervention starting in 2012 aimed to address this gap by providing best management practice (BMP) training for pond based tilapia monoculture and tilapia-mullet polyculture fish farmers. A series of field-based training modules were developed and designed with the participation of leading fish farmers and delivered through private sector farmer-trainers to over 2400 fish farm owners and managers. This paper reports on the results of an impact assessment survey carried out in 2015 comparing fish farm performance, production and profitability in randomly selected farms where the manager had received and was applying the principles of BMP training (BMP) and farms where the manager had not received IEIDEAS project training (control). The results show that although the two groups were very similar in terms of general farm characteristics, BMP farms were more likely to practice tilapia-mullet polyculture than monoculture of tilapia. The main BMP training messages apparent in the results were improved feed and fertilizer management. This resulted in more efficient food conversion ratios in BMP farms compared to control farms. Average fish yields and values were similar between the two groups, although BMP farms produced less small-sized tilapia and more mullet than the control farms. Lower feed costs resulted in significantly lower operating costs in BMP farms compared to control farms, whereas fixed costs were similar for the two groups. Average net profits were significantly higher in BMP farms compared to control farms equivalent to additional profits of over $15,000 for an average farm size of 7.5 hectares. Taking into account the number of farmers trained and BMP adoption rates suggests that $18.9 million additional profits were generated through the intervention in 2014. The results demonstrate that fish farms in mature aquaculture systems can benefit significantly from the adoption of improved farm management practices suggesting that similar approaches, including field-based BMP training and the use of private sector farmer-trainers should be used to accelerate the development of nascent aquaculture sectors in other parts of Africa.